Phylogenetic relationships within Nephtyidae (Polychaeta, Annelida) - Ravara, Ascensão (2010)
We present the first phylogeny of nephtyids, a common, soft-bottom living polychaete family comprising five genera and over 100 species. Characters used to distinguish nephtyid genera are a matter of controversy and considerable confusion remains as to the generic delineations. The phylogeny is estimated with molecular data from the mitochondrial genes cytochrome oxidase I and 16S rDNA, the nuclear genes 18S rDNA and 28S rDNA and morphological data. The results reveal two well-supported major clades, corresponding in part to the two main genera of the family, Aglaophamus and Nephtys. The species Nephtys pulchra and Nephtys australiensis are transferred to Aglaophamus, and new diagnoses for the genera are provided. Dentinephtys is synonymized with Nephtys, and Nephtys cornuta is sister to the remaining nephtyids and is referred to the new genus Bipalponephtys, together with Nephtys danida and Micronephthys neotena. Micronephthys is sister to Nephtys and Inermonephtys is of uncertain position.